The impact of 9/11 and the London bombings on the employment and earnings of U.K. Muslims - Faisal Rabby; William M. Rodgers (Institute for the Study of Labor (IZA), 2010)
Using a difference-in-differences framework, this paper estimates the impact that Britain's July 2005 bombings had on the labor market outcomes of UK residents who are either Muslim by religious affiliation or whose nativity profiles are similar to the terrorists. We find a 10 percentage point decrease in the employment of very young Muslim men relative to non-Muslim immigrants after the London bombings. The drop in employment is accompanied by consistent declines in real earnings and hours worked. A weak association between the 9-11 terrorist attacks and a drop in the employment of very young male immigrants from Muslim-majority countries is also found. The terrorist events had little impact on the employment of older men.
Keywords: J15; J23; J61; J71; 330; Muslim; ethnic minority; minorities; 9/11; employment; London bombings; Politische Gewalt; Islamisch; Lohndifferenzierung; Muslime; Jugendliche Arbeitskräfte; Beschäftigungseffekt; Großbritannien